El Llibre de cetreria del vescomte de Rocabertí. - OLMOS DE LEÓN, RICARDO M.; FERRAGUD, CARMEL (Scripta, 2021)
In this article we offer a critical edition of Llibre de cetreria [Book of falconry], a brief treatise of falconry written in Catalan. It is kept as a sole manuscript belonging to a private collection. We study its structure and content, as well as its relations with other falconry archive teatrises, namely those written in the Crown of Aragon. We formulate a hypothesis about the authorship and the age when the treatise was written. This is the Catalan treatise naming the greatest number of birds of prey. Hence, in this edition we offer a thorough exposition of the birds used by hunters, and the related terminology that was developed in Catalan.